Awareness regarding oral health among women with polycystic ovary syndrome: a qualitative study - K., Nivedha; S., Aparna; Madankumar, Parangimalai Diwakar (International Journal Of Community Medicine And Public Health, 2023)
Polycystic ovary syndrome (PCOS) is a common endocrine disorder among women of reproductive age. The PCOS primarily affects the reproductive system, with substantial collateral negatively health effects on metabolic, psychologic, and cardiovascular functions. Women with PCOS have increased pro-inflammatory cytokine levels, and this inflammation can lead to several “oral health problems” which are often ignored by patients. This qualitative study aims to explore the knowledge and the impact of oral health in women with PCOS. An in-depth interview was conducted among women with PCOS (aged between 18-35 years) who were diagnosed based on the Rotterdam’s criteria, within the time period of July 2021 to August 2021. Sampling was purposive and continued until data saturation was reached. Data were analysed using the thematic analysis technique with NVIVO 10.0 software (Numerical Analytics Instruments). The analysis of the data helped to extract the main theme of the research as “PCOS impact on oral health” under 3 main category themes and 8 sub-category themes. There is a need for education at the community level to increase general awareness and to understand the condition. Better awareness could also help women to recognise possible symptoms and prompt them to seek help, leading to more timely diagnoses.